Specific Features of The Clinical Manifestation of Ischemic Heart Disease in Medical Professionals - Usmanovna, Nazarova Gulchekhra; Solievich, Mamasoliyev Nematjon; Shukhrat kizi, Madumarova Zarnigor; Yakubovich, Bustanov Sherzodbek (Journal of Neonatal Surgery, 2025)
Background: Ischemic heart disease (IHD) is a leading cause of morbidity and mortality globally . Healthcare professionals, including physicians and nurses, are not immune to this burden. This article examines how IHD manifests in medical professionals and the unique epidemiological and clinical features in this population. Methods: A narrative review of recent literature (last 10 years) was conducted, focusing on epidemiological studies, risk factor analyses, and clinical reports pertaining to IHD among healthcare workers. Results: Medical professionals show distinctive patterns: epidemiological data suggest that physicians often have fewer traditional risk factors and lower rates of major cardiac events than the general population , yet they experience significant occupational stressors (long work hours, shift work, and burnout) that heighten cardiovascular risk . Unique challenges include atypical symptom presentations and delays in seeking care due to self-diagnosis or underreporting. Conclusions: IHD in medical professionals is influenced by a complex interplay of professional habits and occupational hazards. Tailored strategies – from improved screening and self-care to institutional policies limiting work hours – are recommended to address these challenges. Ultimately, protecting the heart health of healthcare providers is vital, both for their well-being and the quality of care they deliver.